DECODING TIME HONORED TRADITIONAL ROGAN ART THROUGH THE LENS OF DESIGN PRINCIPLES - Sunil, Shruti; Kumar, Ashwin; Ganeshgudi, Abhishek (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rogan art is a time honored Indian traditional art. In India, Gafur family in Kutch, Gujarat, only practices it. The Rogan art is performed live without using any prior designs. They are painted on fabric using color made from castor oil and natural pigments. The Rogan artisan faces difficulties in selling their products due to the unavailability of an organized market. Due to which, the young generation are not willing to practice this traditional art making it at the verge of extinction. As a design student, I found Rogan art to be a perfect blend of traditional knowledge and cultural heritage. Its vibrant colors and intricate designs make it distinct from other art forms. The use of natural colors and oil offers us the opportunity to explore sustainability, which is the need of this hour. In this paper, I tend to study Rogan art and artisan’s creativity through the lens of design principles.